1991
DOI: 10.1139/f91-176
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Distributions in Aquatic Insects: Variations among Genera, Elements, and Lakes

Abstract: The distribution patterns of trace element contaminants (As, Cd, Cu, Pb, Zn) among the tissues of freshwater insects (Chironomus, Clinotanypus, Procladius, Hexagenia, Sialis) are both taxon and element specific. In quantity terms (micrograms per animal), the gut is the major organ of Cd accumulation, while most of the As, Cu, Pb, and Zn accumulates in the body (i.e. animal minus gut and other organs). In concentration terms (micrograms per gram), Cd, Cu, and Zn are often highest in the gut, while Pb and As are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 28 publications
2
26
2
1
Order By: Relevance
“…[33] Arsenate is additionally found, albeit at low levels, in the anterior foregut (Fig. 2h), a region that is relatively low in As III (SR) 3 .…”
Section: Arsenic Speciation Using X-ray Absorption Spectroscopymentioning
confidence: 97%
“…[33] Arsenate is additionally found, albeit at low levels, in the anterior foregut (Fig. 2h), a region that is relatively low in As III (SR) 3 .…”
Section: Arsenic Speciation Using X-ray Absorption Spectroscopymentioning
confidence: 97%
“…Furthermore, zinc concentrations in chironomids generally did not show an increase with increasing sediment zinc (SEM zinc) concentration, suggesting either that zinc was not bioavailable, that chironomids were capable of actively regulating zinc concentrations in their tissues, or both. Since zinc is an essential element and since chironomids are capable of regulating zinc body burdens [38,39], both explanations seem probable. In addition, the mean zinc tissue concentrations recorded in this study (1.4-12.0 mol/g) are comparable to total chironomid tissue concentrations reported by other researchers.…”
Section: Zinc Bioaccumulation By Benthic Macroinvertebratesmentioning
confidence: 99%
“…More over it was found that concentrations of Cadmium were lower in shell than the corresponding values in soft tissue. This seems to be a common behavior for many aquatic organisms (Hare et al, 1991;Abdel Gawad, 2001& 2005, where the exoskeleton of contaminated organisms contains smaller amounts of trace metals relative to internal parts. …”
Section: Discussionmentioning
confidence: 99%